Class D amplifier with pseudo-randomized carrier frequency modulation (PRCFM) for EMI mitigation - Jin, Chongfei (2015)
Class D amplifiers are found in nearly all portable electronic products for their small size and power efficiency. Due to their high frequency switching operation, they generate significant amount of electromagnetic interference (EMI) and usually off-chip filters are necessary in order for them to comply with the international regulatory EMI limits. With the continuous trend of product miniaturization, filter-less Class D amplifiers are gaining attention recently. Without the off-chip filter, designing a fully integrated filter-less Class D amplifier to meet the EMI requirements can be challenging.